Exploring the culturally sensitive sexual and reproductive health information communication skill needs of parents in Ghana - Frank B. Agyei; Doreen M.K Kaura; Janet D. Bell (AOSIS, 2023)
Background: Parents play a vital role in the sexual and reproductive health (SRH) of adolescents. Parents' communication with their adolescents regarding SRH is considered an important part of adolescent development, as this contributes to optimising safe SRH. Aim: This phase of the study explored the culturally sensitive SRH information communication skill needs of parents, based on their personal and social motivation, within the Ghanaian context. Setting: The study was conducted at the Asante Akyem North Municipality of Ghana. Methods: This article describes the second phase of an explanatory, sequential, mixed-method study. Following on from the first phase systematic review, this second phase comprised a qualitative descriptive study where 10 purposively sampled parents of adolescents participated in semi-structured interviews to elicit data. Braun and Clarke's thematic data analysis process was applied. Data were saved and managed in Atlas.ti (version 23.0.7). Results: Four themes emerged on communication skills: SRH information, parent and adolescent factors, contextual factors and communication skill needs. Parent and adolescent communication on SRH takes place occasionally. Parents lack the skills to communicate with adolescents regarding SRH. Conclusion: Parents in this context require skills to communicate SRH information with their adolescent children. A culturally appropriate intervention that supports SRH information communication between parents and adolescents may have value in guiding this communication process. Contribution: The findings of this study can contribute to the adaptation of a culturally sensitive SRH information communication intervention in Ghana which will promote adolescent SRH.